2021
DOI: 10.1177/15589447211049517
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Management of Pediatric Trigger Thumb in the United States

Abstract: Background: Recent literature suggests that initial observation of pediatric trigger thumb without early surgical interventions can lead to spontaneous resolution. We sought to analyze current trends in the management of pediatric trigger thumb and compare real-world data with what the literature supports. Methods: We conducted a retrospective study of data collected using the PearlDiver database between 2015 and 2018. Patients who were aged younger than 10 years with a diagnosis of trigger thumb were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
(72 reference statements)
2
0
0
Order By: Relevance
“…Regarding factors that are predictive of surgery, a recent large national claims database study by Park et al 13 looked at treatment trends in 997 patients, with 69% falling between the ages of 2 and 5 years, similar to our cohort (64.7%). The rate of surgical intervention in their study was 49%.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Regarding factors that are predictive of surgery, a recent large national claims database study by Park et al 13 looked at treatment trends in 997 patients, with 69% falling between the ages of 2 and 5 years, similar to our cohort (64.7%). The rate of surgical intervention in their study was 49%.…”
Section: Discussionsupporting
confidence: 70%
“…6,12 There are also factors inherent to the patient's condition that are not controllable, such as baseline degree of interphalangeal joint contracture, that may negatively affect the outcome of nonoperative management strategies. 11 Regarding factors that are predictive of surgery, a recent large national claims database study by Park et al 13 looked at treatment trends in 997 patients, with 69% falling between the ages of 2 and 5 years, similar to our cohort (64.7%). The rate of surgical intervention in their study was 49%.…”
Section: Discussionsupporting
confidence: 63%
“…In a study conducted in the United States, it was reported that 69% of patients were diagnosed with trigger thumb between the ages of 2 and 5 years. 23) In our study, the mean age at initial diagnosis was 2.76 ± 1.91 years, and 86.9% of patients were diagnosed with TDs till the age of 5 years. We found that the diagnoses of pediatric TDs decreased rapidly after the age of 5 years.…”
Section: Discussionmentioning
confidence: 53%
“…Park et al 23) reported that 49% of the patients underwent surgery for trigger thumbs in the United States: 65% of the patients underwent surgery within 1 year of diagnosis, and 76% of the patients underwent surgery before the age of 5 years. In our study, patients with pediatric TDs underwent surgery at an average age of 3.79 ± 2.19 years.…”
Section: Discussionmentioning
confidence: 99%